2015
DOI: 10.1038/srep11572
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and evolution of cytochrome P450 monooxygenases in Oomycetes

Abstract: Cytochrome P450 monooxygenases (P450s) are heme-thiolate proteins whose role as drug targets against pathogens, as well as in valuable chemical production and bioremediation, has been explored. In this study we performed comprehensive comparative analysis of P450s in 13 newly explored oomycete pathogens. Three hundred and fifty-six P450s were found in oomycetes. These P450s were grouped into 15 P450 families and 84 P450 subfamilies. Among these, nine P450 families and 31 P450 subfamilies were newly found in oo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
67
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(74 citation statements)
references
References 53 publications
7
67
0
Order By: Relevance
“…P450 blooms were observed in animals, especially in arthropods, mainly insects (Feyereisen 2011), fungi (Syed et al 2013, and oomycetes (Sello et al 2015) where certain P450 families bloomed because of the organisms' need. Considering the lowest number of P450s and large number of P450 families, it is reasonable to expect no P450 blooming in the two model algal species.…”
Section: Resultsmentioning
confidence: 99%
“…P450 blooms were observed in animals, especially in arthropods, mainly insects (Feyereisen 2011), fungi (Syed et al 2013, and oomycetes (Sello et al 2015) where certain P450 families bloomed because of the organisms' need. Considering the lowest number of P450s and large number of P450 families, it is reasonable to expect no P450 blooming in the two model algal species.…”
Section: Resultsmentioning
confidence: 99%
“…Both FGNX-2 and non-NX-2 producers had the EggR motif ( Figure 5). Sello et al [31] analyzed the ExxR motif among oomycetes and found that the first and fourth residues, i.e., "E" and "R" are conserved in all P450 families, e.g., CYP5014, CYP5015, and CYP5017. There are a few exceptions; in CYP5017F8, the motif consisted of a "K" instead of "E" and in CYP5014N1 and CYP5015L, the motif consisted of "W" and "H", respectively, instead of "R".…”
Section: Per/pxrw and Exxr Motifsmentioning
confidence: 99%
“…Varga et al [22] analyzed amino acid sequences of F. graminearum DON-producers and F. graminearum NX-2 producers and found that NX-2 producers had a distinct heme binding motif according to a 20 amino acid heme binding motif. Sello et al [31] analyzed the heme motif across three P450 families and reported that amino acid residues "F", "G" and "C" located as the first, fourth, and eighth positions in the heme motif are conserved in among P450s across biological kingdoms [32], but there are some P450s with different amino acids at these positions [42].…”
Section: Heme Motifmentioning
confidence: 99%
“…The three brown algae share six families, the three diatoms share three families, and all the brown algae, diatoms and N. gaditana share only two families, whereas they have none in common with the oomycetes P. ramorum and P. sojae. As oomycetes P450s have been already reported (Sello et al 2015), we focused in this study on brown algae and diatoms.…”
Section: Identi Fied Cypomes In Stramenopile Speciesmentioning
confidence: 99%
“…The recently cloned CYP5164B1 in the brown alga Ectocarpus siliculosus converts 9 and 13-hydroperoxides of linoleic acid into oxylipin epoxyalcohols (Toporkova et al 2017). Besides, blooming of CYPs in oomycetes has been reported with respect to their diversity and duplications, suggesting a role in adaptation of oomycetes to diverse ecological niches (Sello et al 2015). However, stramenopile P450 diversity remains relatively unexplored, especially in the recently sequenced brown algae and diatoms.…”
Section: Introductionmentioning
confidence: 99%